Proteomic and metabolomic analyses reveal the novel targets of spermine for alleviating diabetic cardiomyopathy in type II diabetic mice - Sun, Jian; Xu, Jiyu; Liu, Yong; Xu, Xiaoyi; Zhang, Shumin; Hao, Yankun; Lin, Yitong; Han, Yue; Li, Feiya; Yuan, Hui (Frontiers in Cardiovascular Medicine, 2022)
Diabetic cardiomyopathy (DCM) is one of the most serious complications of diabetes. Recent cardiology studies suggest that spermine has cardioprotective effect. Here, we used proteomics and metabolomics analyses to reveal the underlying research target in type 2 diabetic mouse model treated with spermine. Left ventricular tissue was excised from 9 mice (Control group, 3; T2D group, 3; T2D+SP group, 3) and analyzed. Quantitative analysis of the global proteome and metabolome were detected using 4D label-free technique and untargeted metabolomics, respectively, and differentially expressed proteins (DEPs) and metabolites were used to perform bioinformatic analyses. A total of 169 DEPs were identified in T2D/Control group, including 115 upregulated and 54 downregulated proteins. Furthermore, 16 DEPs were determined in T2D/T2D+SP group and proteomic analysis revealed that the two group DEPs were highly enriched in the cellar process, metabolic process, biological regulation, response to stimulus, immune system process, and the ferroptosis and PPAR signaling pathway. The results of association analysis between proteomics and metabolomics showed that SP could regulate the production of 51 metabolites by the expression of 16 DEPs. Moreover, PRKG1 was closely related to the expressions of 10 overlapping metabolites between db/db and SP-treated mice. Our findings indicate new valuable information on underlying mechanisms for DCM, and suggest spermine have potential applicability to protect against deterioration of cardiac function with DCM.